Repetitive climbing effect on muscle activation - Pettersson, V. (University of Halmstad, 2020)
Background. Climbing is growing as a recreational sport worldwide. Climbing is a physically demanding sport requiring well developed strength and endurance. Plenty of studies have been made in the area of climbing in order to understand how the body adapts, which muscles are being used and how to prevent injury. A lot of these studies uses electromyography (EMG), a tool that measures electrical currents in muscles to detect muscle activity,as measurement method in order to do findings within the area. Aim. The aim was to study differences in muscle activation in arm and leg muscles in climbers before and after 40 repeated attempts over two weekson a boulder problem. Furthermore, correlation between climbing level and change in total measured muscle activation after repeated attempts was assessed. Methods. 15 participants (five women and ten men) participated in this study. Standardized electrode placements and maximal voluntary isometric contractions (MVIC) were made for muscles; Flexor Carpi Radialis (FCR), Bicep Brachii (BB), Rectus Femoris (RF) and Gastrocnemius Lateralis (GL) before each measurement in order to maintain good reliability. Participantsrepeated a specific climbing route, adapted to the participants climbing ability, 40 times, divided into four sessions over two weeks.Before the first measured attempt the participant got to practice the route twice to get familiar with the moves. Average muscle activation was calculated by dividing the total muscle activation from each muscle with the time it took to complete the climbing route. Peak muscle values were calculated by dividing thehighest muscle activation value with the MVIC values to get a %MVIC value. Results. A decrease in average muscle activation for FCR and BB were found (p=0.038, 0.023) whereas an increase in average activation for GL was found (p=0.027).Peak muscle activation showed significant decreases regarding upper extremities FCR and BB (p=0.008, p=0.011) but no significant changes to lower extremities RF and GL.Total average muscular activation regarding all muscles combined showed a general decreased activation (p=0.001). Moderate correlation was found between red-point level and decrease in total average muscle activation(r=0.53). Conclusion.When repeating a climbing route, the climbers muscle activation differs in upper and lower extremities, with a decrease inupper extremities peak and average muscle values, and an increase in GL average muscle values. Repetitions improves technique and muscle memory which could be the reason for the overall decrease in total muscle activation. Hopefully, this study could enrich the climbing world with further knowledge in how to train for climbing.